Clinical Management of Adverse Events Associated with Lorlatinib. (19th March 2019) - Bauer, Todd M.; Felip, Enriqueta; Solomon, Benjamin J.; Thurm, Holger; Peltz, Gerson; Chioda, Marc D.; Shaw, Alice T.
Abstract: : Lorlatinib is a novel, highly potent, brain‐penetrant, third‐generation ALK/ROS1 tyrosine kinase inhibitor (TKI), which has broad‐spectrum potency against most known resistance mutations that can develop during treatment with crizotinib and second‐generation ALK TKIs. The safety profile of lorlatinib was established based on 295 patients who had received the recommended dose of lorlatinib 100 mg once daily. Adverse events associated with lorlatinib are primarily mild to moderate in severity, with hypercholesterolemia (82.4%), hypertriglyceridemia (60.7%), edema (51.2%), peripheral neuropathy (43.7%), and central nervous system effects (39.7%) among the most frequently reported. These can be effectively managed with dose modification and/or standard supportive medical therapy, as indicated by a low incidence of permanent discontinuations due to adverse reactions. Most patients (81.0%) received at least one lipid‐lowering agent. Prescription of supportive therapy should also consider the potential for drug‐drug interactions with lorlatinib via engagement of specific CYP450 enzymes. This article summarizes the clinical experience from lorlatinib phase I investigators and was generated from discussion and review of the clinical study protocol and database to provide an expert consensus opinion on the management of the key adverse reactions reported with lorlatinib, including hyperlipidemia, central nervous system effects, weight increase, edema, peripheral neuropathy, and gastrointestinal effects. Overall, lorlatinib 100 mg once daily has a unique safety profile to be considered when prescribed, based on the recent U.S. Food and Drug Administration approval, for the treatment of patients with ALK‐positive metastatic non‐small cell lung cancer previously treated with a second‐generation ALK TKI. Abstract : This article provides recommendations for the clinical management of key adverse reactions reported with lorlatinib.